Party organisation and polity-wide parties in India - Shrimankar, Dishil (2018)
Why do polity-wide parties in a multi-level context dominate in some sub national units but not others? Existing scholarship in comparative politics has either focused on regionally-based social cleavages or on political and economic decentralisation to explain the variation in the dominance of polity-wide parties at the sub-national level. Deviating from this predominant approach in comparative politics, I argue that political and economic decentralisation and the presence of distinct regional cleavages are necessary, but not sufficient conditions to explain the dominance of polity-wide parties. In other words, polity-wide parties are able to maintain their dominance at the sub-national level in a politically and economically decentralised polity with distinct sub-national regional cleavages if their sub-national branches have autonomy from their central branches.